Household Food Security State and its Determinant in the Chepang Tribe in Chitwan: An Ordered Probit Analysis - Pandey, Sweta; Thapaliya, Krishna Prasad (Journal of Agriculture and Forestry University, 2026)
The livelihoods of the Chepang community depend largely on agriculture and natural resources, leaving them highly vulnerable to climate-induced shocks and food insecurity. Despite this vulnerability, empirical evidence assessing food security and its determinants among the Chepang population remains limited, particularly studies that account for varying levels of food insecurity. The present study addresses this gap by evaluating household food security using the widely adopted Food Consumption Score (FCS) and identifying its key determinants through an ordered probit regression model. A mixed-methods design was employed. Data were collected in 2024 from 120 randomly selected Chepang households in Kalika Municipality, Chitwan, complemented by one focus group discussion and five key informant interviews. The findings revealed that 42.50% of households achieved an acceptable food consumption level, while 21.67% were classified in the poor food consumption category based on the FCS. Results from the ordered probit model indicated that the gender of the household head and landholding size were significant determinants of household food security. Female-headed households were more likely to fall into the poor food consumption category (p < 0.05), whereas households with larger landholdings were significantly more likely to attain acceptable food consumption levels (p < 0.01). The study recommends policy interventions that enhance secure land access for asset-poor households and promote gender-inclusive capacity-building programs to strengthen food security and resilience among the Chepang community.